Empathy and embodied experience in virtual environment: To what extent can virtual reality stimulate empathy and embodied experience? - Shin, Donghee (Computers in human behavior, 2018)
This study investigates the user experience to clarify what it is like to experience stories in VR (virtual reality) and how immersion influences story experiences in immersive storytelling. This study explores the immersive storytelling context, developing and testing a VR experience model that integrates presence, flow, empathy, and embodiment. The results imply that users’ personal traits correlates immersion in VR: user experience in VR depend on individual traits, which in turns influence how strongly users immerse in a VR. The way users view and accept VR stories derives from the way they envisage and intend to experience them. Rather than simply being influenced by technological features, users have intentional and purposeful control over VR stories. The findings of this study suggest that the cognitive processes by which users experience quality, presence, and flow determine how they will empathize with and embody VR stories. •User experience of virtual reality storytelling.•How immersion influences story experiences in immersive storytelling.•Users' personal traits correlates immersion in VR.•The way users view and accept VR stories derives from the way they envisage and intend to experience them.